Patient experiences with hidradenitis suppurativa: the Hidradenitis Patient Experience survey. (26th August 2021) - Kashetsky, N.; Mukovozov, I. M.; Pereira, J.; Manion, R.; Carter, S.; Alhusayen, R.
Summary: Background: Better understanding of the experience of people living with hidradenitis suppurativa (HS) is essential to identify gaps in current patient care and inform healthcare decision‐making. Aim: To describe the patient experience of individuals with HS, including their path to diagnosis, symptom control, treatments, healthcare utilization, patient needs and impact on quality of life. Methods: The Hidradenitis Suppurativa Patient Experience survey was created, extensively reviewed and disseminated through engaging HS‐related patient organizations, physician groups and social media groups. Results: In total, 537 respondents completed the survey; the mean age was 38 years (range 14–73 years) and 95% (510 of 537) were female. The mean number of treatment types per respondent was 15, and included antibacterial soaps (93.3%; 431 of 462), avoidance of tight clothing (90.9%; 419 of 462), use of oral antibiotics (79.7%; 368 of 462), nonprescription drugs (79.7%; 368 of 462) and topical antibiotics (77.1%; 356 of 262). Pain was poorly controlled in 46% of respondents (184 of 401). HS had a negative impact on the ability to work and attend school for 81% of respondents (337 of 415), with 59% (245 of 415) missing at least 2 days of work a month and 16% (66 of 415) missing > 11 days of work. The mean number of misdiagnoses per respondent was three and the median time to diagnosis was 10 years. Conclusion: Individuals with HS experience a delay in diagnosis and have suboptimal control of the disease. We propose 11 recommendations to improve diagnosis, treatment and quality of life for individuals living with HS.